Developing Systemic Contributors and Adaptations Diagramming (SCAD): systemic insights, multiple pragmatic implementations. (September 2022) - Jefferies, Christine M.; Asher Balkin, E.; Groom, Luke; Rayo, Michael F.
Traditional event exploration techniques in safety operations such as RCA and FMEA focus on developing explanations of specific events and in so doing, risk producing over-simplified highly linearized models of organizational behavior which are largely divorced from the realities of the work. Techniques such as FRAM, STAMP, and AcciMap, produce highly accurate models of system behavior but are often prohibitively resource intensive. These difficulties have made the types of inquiry which can inform Safety-II-style analysis difficult and expensive. In a review of four recent studies, we discuss implementation of the Systemic Contributors and Adaptations Diagramming (SCAD) framework, demonstrating its value in rapidly identifying useful cases, engaging a wider range of organizational roles, and arriving at useful insights more quickly and with reduced resource burden. Rather than focus on a specific event, SCAD explores the distribution of pressures across the system and the associated adaptive behaviors which employees undertake to address those pressures.